Clinical efficacy of hyaluronic acid in post-extraction sockets of impacted mandibular third molar - Sairan Khurshed Nariman; Reiadh Kamal AL-Kamali (Erbil Dental Journal)
Background and Objectives: Pain and swelling are the most common complications that occur after surgical removal of impacted third molar. Aim of this study to evaluate the effectiveness of local hyaluronic acid (HA) administration to surgically remove impacted third molar sockets to evaluate pain and swelling. Materials and Methods: A comparative study included 50 healthy patients were subdivided into two equal sub group, aged 18-35 years with impacted lower third molars type of impaction (class II; position B according to Pell–Gregory classification). The procedure has been performed under local anesthesia. In the study group, 0.8% HA (Gengigel®) was applied in the post-extraction sockets of third molars and in the control group nothing was applied to the extraction sockets of third molars. Pain and swelling were evaluated with a visual analogue scale (VAS). Assessments were made on 1st, 2nd, 3th, 4th, 5th, 6th, 7th days after surgery. Results: Statistically significant difference was detected for the pain values between the two treatment groups in different days of the study (p < 0.05). The swelling scores of the hyaluronic acid group were significantly lesser than those of the control group in day 1 (p = 0.008), day 3 (p = 0.006), and day 4 (p = 0.036). In the other days, the scores were less but the differences were not significant. Conclusion: hyaluronic acid appears to offer a beneficial effect in the management of pain and swelling during the immediate postoperative period following impacted third molar surgery.